If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4x + -8) = 12 Reorder the terms: -2(-8 + 4x) = 12 (-8 * -2 + 4x * -2) = 12 (16 + -8x) = 12 Solving 16 + -8x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -8x = 12 + -16 Combine like terms: 16 + -16 = 0 0 + -8x = 12 + -16 -8x = 12 + -16 Combine like terms: 12 + -16 = -4 -8x = -4 Divide each side by '-8'. x = 0.5 Simplifying x = 0.5
| 2m+1=27 | | 6x+x-8=6x+7 | | 11k-11=7k-(-21) | | (8x^2+2x-6)-(5x^2-3x+2)=0 | | 2g-4=-8 | | 2(x-1)-3x=7 | | 15/x+5*3=40+6x | | 4a^2-16a^2=0 | | 3x+5=-1x-7 | | y^2-2y+1=64 | | Y=Go+d | | 800+160-30=0 | | 2(x+20)=2(x-10) | | 5/6x=-218 | | 7/5x=3/10 | | (x)(x-2)=35 | | Sin^2(X)=2cosx | | 800(100+30)=0 | | 102=(x+18)+(x-12)+x | | -x+13=x+6 | | 21d=-63 | | 56x=-218 | | M=57 | | -5y+10x=-15 | | 168=-6(8x-4) | | 4p(p+2)=0 | | 665/7 | | 4(n-3)=28 | | -3(-3+5x)=-6 | | -7(2x-6)=154 | | -9x+5x=16 | | 6(-3+2b)=-90 |